SwimOne. New Device for Determining Instantaneous Power and Propulsive Forces in Swimming - Hermosilla, Francisco; Corral Gómez, Lis; González Ravé, José María; Juárez Santos-García, Daniel; Rodríguez Rosa, David; Juárez Pérez, Sergio; Castillo García, Fernando J. (My University, 2020)
The propulsive forces and instantaneous power that are generated by a swimmer have a great influence on the swimming performance. This works presents a new device, called SwimOne, for measuring propulsive force and estimating the instantaneous power of the swimmer. In addition, the detailed prototype is able to exert a customizable opposition force to the swimmer for training purpose. The conceptual idea is presented by describing the differential equation of the swimmer and the protocol for a factible estimation of the instantaneous power. The variables that are to be measured and estimated are identified and, consequently, the sensor and actuator systems can be selected. The high-level and detailed designs of the prototype are presented together with the protocol that is carried out in order to validate the sensor and actuation systems. The device is able to monitor the variables of interest of the swimmer together with the propulsive force and instant power. Finally, some experiments are carried out providing the results of several participants swimming in crawl, backstroke, butterfly, and breaststroke styles in the presence of different opposition force. The preliminary results show that SwimOne is valid for measuring instantaneous force and power with different loads in swimming. Keywords: training; swimming; force; power; resistance